Enriched Expression of GluD1 in Higher Brain Regions and Its Involvement in Parallel Fiber–Interneuron Synapse Formation in the Cerebellum - Konno, Kohtarou (J Neurosci, 2014)
Of the two members of the δ subfamily of ionotropic glutamate receptors, GluD2 is exclusively expressed at parallel fiber–Purkinje cell (PF–PC) synapses in the cerebellum and regulates their structural and functional connectivity. However, little is known to date regarding cellular and synaptic expression of GluD1 and its role in synaptic circuit formation. In the present study, we investigated this issue by producing specific and sensitive histochemical probes for GluD1 and analyzing cerebellar synaptic circuits in GluD1-knock-out mice. GluD1 was widely expressed in the adult mouse brain, with high levels in higher brain regions, including the cerebral cortex, striatum, limbic regions (hippocampus, nucleus accumbens, lateral septum, bed nucleus stria terminalis, lateral habenula, and central nucleus of the amygdala), and cerebellar cortex. In the cerebellar cortex, GluD1 mRNA was expressed at the highest level in molecular layer interneurons and its immunoreactivity was concentrated at PF synapses on interneuron somata. In GluD1-knock-out mice, the density of PF synapses on interneuron somata was significantly reduced and the size and number of interneurons were significantly diminished. Therefore, GluD1 is common to GluD2 in expression at PF synapses, but distinct from GluD2 in neuronal expression in the cerebellar cortex; that is, GluD1 in interneurons and GluD2 in PCs. Furthermore, GluD1 regulates the connectivity of PF–interneuron synapses and promotes the differentiation and/or survival of molecular layer interneurons. These results suggest that GluD1 works in concert with GluD2 for the construction of cerebellar synaptic wiring through distinct neuronal and synaptic expressions and also their shared synapse-connecting function.